Indonesian-language version of general self-efficacy scale-12 using Bayesian confirmatory factor analysis: A construct validity testing - Muhammad Dwirifqi Kharisma Putra; Wardani Rahayu; Jahja Umar (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
The General Self-Efficacy Scale 12 (GSES-12) is a brief measure for assessing self-efficacy. This study aimed to revise an Indonesian language version of the GSES-12 that was translated and adopted from previous research. The revision conducted by following the Guidelines for the Process of Cross-Cultural Adaptation of Self-Report Measures, and the final version was administered to 303 (132 male, 171 female) Indonesian students, with a mean age of 19.56 years (SD: 1.20). This study is presented to establish the construct validity of this instrument further. The results of Bayesian CFA revealed a higher-order structure of factor representing constructs of self-efficacy. Considering the theoretical background and the best model fit indices (PPP-value = 0.549 and BRMSEA = 0.001), it is concluded that the Indonesian version of GSES-12 appears to be a valid instrument in assessing self-efficacy in Indonesian speaking students and is expected to facilitate the examination of self-efficacy in Indonesian speaking populations.